HIPK3 Inhibition by Exosomal hsa-miR-101-3p Is Related to Metabolic Reprogramming in Colorectal Cancer - Tao, Lihuiping; Xu, Changliang; Shen, Weixing; Tan, Jiani; Li, Liu; Fan, Minmin; Sun, Dongdong; Lai, Yueyang; Cheng, Haibo (Frontiers in Oncology, 2022)
Background: Exosomes are extracellular vesicles secreted by most cells to deliver functional cargoes to recipient cells. MicroRNAs (miRNAs) constitute a significant part of exosomal contents. The ease of diffusion of exosomes renders them speedy and highly efficient vehicles to deliver functional molecules. Cancer cells secrete more exosomes than normal cells. Reports have showed that exosomal miRNAs of cancer cells facilitate cancer progression. Yet the complexity of cancer dictates that many more functional exosomal miRNAs remain to be discovered. Methods: In this study, we analyzed miRNA expression profiles of tissue and plasma exosome samples collected from 10 colorectal cancer (CRC) patients and 10 healthy individuals. We focused on hsa-miR-101-3p (101-3p), a profoundly up-regulated miRNA enriched in plasma exosomes of patients bearing CRC. We performed target analysis of 101-3p and pursued functional studies of this microRNA in two colorectal cancer cell lines, namely HCT116 and SW480. Results: Our results indicated that inhibiting 101-3p slowed cell growth and retarded cell migration in vivo in two colorectal cancer cell lines. Target analysis showed that Homeodomain-interacting protein kinase (HIPK3) is a target of miR-101-3p. HCT116 and SW480 cells stably overexpressing HIPK3 showed increased level of phosphorylated FADD, as well as retarded cell growth, migration, and increased sensitivity to 5-FU. In-depth analysis revealed increased mitochondrial membrane potential upon HIPK3 overexpression along with increased production of reactive oxygen species, number of mitochondria, and expression of respiratory complexes. Measurements of glycolytic parameters and enzymes revealed decreased level of glycolysis upon HIPK3 overexpression in these two cell lines. Xenograft model further confirmed a profoundly improved potency of the synergistic treatment combining both 5-FU and 101-3p inhibitor compared to 5-FU alone. Conclusion: This study unraveled an oncogenic nature of the exosomal 101-3p and suggested a relationship between the 101-3p-HIPK3 axis and metabolic homeostasis in colorectal cancer. Expression level of 101-3p is positively correlated with glycolytic capacity in CRC and therefore 101-3p itself is an oncomiR. Combining 101-3p inhibitor with chemotherapeutic agents is an effective strategy against CRC.